The influence of entrepreneurial culture on enhancing efficiency of industrial entrepreneurship (case study of St. Petersburg Bakers’ Association) - A. S. Zorin; N. A. Zorina; P. A. Safrygin (Омский научный вестник: Серия "Общество. История. Современность")
The article addresses the influence of entrepreneurial culture on enhancing the efficiency of industrial entrepreneurship. As business culture is getting more and more into modern economy, it becomes greatly important to develop a modern organization basing on the principles of entrepreneurial culture. It is particularly relevant for socially responsible industrial organizations including baking companies. The aim of the research is to define principles of entrepreneurial culture that serves as a backbone of entrepreneurship. The objectives of the research include the review of primary activities within the baking industry of St. Petersburg based on the principles of entrepreneurial culture. The article gives the differentiation between entrepreneurial and business culture with the reasoning on key features, as well as analyses the performance of St. Petersburg Bakers’ Association, a non-profit organization, on the principles of entrepreneurial culture